Situating Institutional Responses to Latina Intimate Partner Violence Victims: An Argument for a LatCrit Lens - Garza, Alondra D. (Crime & delinquency, 2021)
Existing critical theoretical frameworks have been useful for understanding institutional responses to intimate partner violence (IPV) among victims of Color. The present theoretical paper extends upon these earlier approaches by using a LatCrit theory and praxis lens to situate institutional responses to Latina IPV victims specifically. Through a LatCrit lens, this essay addresses three interrelated themes that address challenges for Latina IPV victims, including: racialized indeterminacy, hegemonic representation, and the criminal legal system as a racialized organization. Theoretical implications, future research, and recommendations are discussed.